Fortification of bovine milk with natural polyphenols extracted from pomegranate peels - Zam, Wissam (Progress in Nutrition, 2016)
Polyphenols were extracted from Pomegranate peels and then encapsulated by ionic gelation. The aqueous extract and the microbeads were used for the preparation of fortified milk. All beverages were kept in refrigerator and the shelf life of milk in terms of polyphenols content was studied. Results showed that 62.23% of polyphenols remained stable for 11 days in milk fortified with alginate-pectin (2:1) microbeads, while only 38.13% and 5.47% of polyphenols remained stable in milk fortified with sodium alginate microbeads and aqueous extract, respectively. Results also suggest that the formation of milk protein-polyphenol complexes compromises the antioxidant potential of the beverage.